Phagocytic receptors activate and immune inhibitory receptor SIRPα inhibits phagocytosis through paxillin and cofilin - Gitik, Miri; Kleinhaus, Rachel; Hadas, Smadar; Reichert, Fanny; Rotshenker, Shlomo (Frontiers in Cellular Neuroscience, 2014)
The innate-immune function of phagocytosis of apoptotic cells, tissue-debris, pathogens and cancer cells is essential for homeostasis, tissue repair, fighting infection and combating malignancy. Phagocytosis is carried out in the CNS by resident microglia and in both CNS and PNS by recruited macrophages. While phagocytosis proceeds, bystander healthy cells protect themselves by sending a “do not eat me” message to phagocytes as CD47 on their surface ligates immune inhibitory receptor SIRPα on the surface of phagocytes and SIRPα then produces the signaling which inhibits phagocytosis. This helpful mechanism becomes harmful when tissue-debris and unhealthy cells inhibit their own phagocytosis by employing the same mechanism. However, the inhibitory signaling that SIRPα produces has not been fully revealed. We focus here on how SIRPα inhibits the phagocytosis of the tissue-debris “degenerated-myelin” which hinders repair in axonal injury and neurodegenerative diseases. We tested whether SIRPα inhibits phagocytosis by regulating cytoskeleton function through paxillin and cofilin since (a) the cytoskeleton generates the mechanical forces that drive phagocytosis and (b) both paxillin and cofilin control cytoskeleton function. Paxillin and cofilin were transiently activated in microglia as phagocytosis was activated. In contrast, paxillin and cofilin were continuously activated and phagocytosis augmented in microglia in which SIRPα expression was knocked-down by SIRPα-shRNA. Further, levels of phagocytosis, paxillin activation and cofilin activation positively correlated with one another. Taken together, these observations suggest a novel mechanism whereby paxillin and cofilin are targeted to control phagocytosis by both the activating signaling that phagocytic receptors produce by promoting the activation of paxillin and cofilin and the inhibiting signaling that immune inhibitory SIRPα produces by promoting the inactivation of paxillin and cofilin.